POSSIBILITY OF CIVIL AIRCRAFT IN-FLIGHT REFUELING - A. I. Zhelannikov; A. N. Zamyatin (Научный вестник МГТУ ГА, 2016)
With application of the developed calculation-software package there were conducted the researches, demonstrating the possibility of in-flight refueling of civil aircraft. As a flying tanker there were chosen tanker aircraft ILyushin-78 which is currently operated and a perspective tanker on the basis of ILyushin-96-400T aircraft. Perspective aircraft MC-21-400 was chosen as an aircraft to be refueled.